Identification of the Types of Parched Areca Seed by Near Infrared Spectroscopy - Xue, J.T.; Wu, C.J.; Wang, L.L.; Zhang, J.L.; Huang, G.; Jiang, S.; Wen, S.L.; Liang, Y.; Chao, R.B.; Chen, C.; Ye, L.M. (Asian Journal of Chemistry, 2011)
This research was aimed to establish a rapid and automated analytical method for the identification of different types of parched areca seed (AS) (raw areca seed, parched-yellow areca seed, seorched areca seed and charring areca seed) by near infrared spectroscopy (NIR). Twenty kinds of areca seed were selected from 60 kinds obtained from various places and then were parched by an online-type and non-contact temperature measurement system invented by our study team; based on the colour, parching temperature and time, concentration of main effective constituent and the results of cluster analysis of 290 samples. The near infrared identification model which could identify four types of parched areca seed fast and accurately was establish after pretreated with vector normalization and first derivative method. The proposed method is accurate and robust which could be used for the identification of other traditional Chinese medicine.